Currículo com música: normaliza ou faz dançar? - Camila Amorim Campos (2018)
Songs are present in the most different spaces, including school. There are songs in school through several musical genders: songs of roda, axé, forró, funk, pop rock, reggae, Brazilian Popular Music (MPB), childrens songs, samba, pagode, sertanejo, gospel, soccer hymns, rap, etc. They can be brought by children, or are worked through teachers proposals. Songs are also chosen for being played on parties and celebrations, on the playtime and physical education. Thus, through many ways, music is strongly present on schools daily routine. This Masters dissertation analyses what the songs do on curriculum and what curriculum does with the songs on the three first years of Elementary School. So, once Ive been inspired on post-critical curriculum studies - which come as a social construction that is crossed by power relations that produce subjects, and also as a territory of possibilities - the general argument I developed in this dissertation is that, on one hand, there are, on the investigated curriculums, different norms and orders that determine what songs can be sung and what from them must be silenced in this curricular space. In another hand, however, there are also children who, at some moments, resist to those orders, it means, they sing other kinds of songs and they can, then, produce some desestabilization, not just to the norms, but also for the curriculum functioning as well. This dissertation shows that, on the investigated curriculum, children are taught to sing some kind of songs which normalize their actions. These subjects sing, thus, in accordance with what is expected by the teachers. The children, however, try to scape from the routine which is forged by school, what according to it some songs are allowed to be sung at certain times. Then, the analysis which are presented here give us the evidence that, although all the investiments to normalize and regulate bodies, children find gaps in curriculum and invite it to dance. The current dissertation also shows that, when a different rhythm comes in the curriculum, it extricates and tries to silence the sound, but it the curriculum - are not able to silence the meaning which children give to that moment. The research also gives us the evidence that songs are useful for children to break up with gender norms at the june party and, then, make dance happen. Moreover, this work presents how the curriculum itself, in composition with music, goes through conflits with its own orders and silence. The research shows, therefore, that this composition, between curriculum and music, is a territory for norms and also a field for breaking the orders and, then, to reinvent life with new flavors. It is a composition that normalizes and also makes dance happen